Turkey : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report ;, 2021)
In Turkey, as in other countries, the human and economic toll of the COVID-19 pandemic has been severe. Thousands of lives have been tragically lost and many livelihoods compromised. The initial policy response to the pandemic-and subsequent sharp growth rebound-set Turkey apart from its peers. Rapid monetary and credit expansion and large liquidity support meant that Turkey was among the few countries to experience positive economic growth in 2020. But these policies also aggravated pre-existing economic and financial vulnerabilities. Higher inflation, increased dollarization, and a large shift in the current account position increased pressure on the lira and gave rise to heavy foreign exchange sales, which led in turn to steep reserve declines from already-low levels. A policy shift in late 2020-mainly towards tighter and more transparent monetary policy and slower credit growth-was both welcome and necessary. But the durability and depth of the shift were called into question in March 2021, following the change in central bank leadership, as the lira weakened markedly and interest rate spreads widened.